2017
DOI: 10.1007/s11845-017-1692-y
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA TRPM2-AS as a potential biomarker for hepatocellular carcinoma

Abstract: Background There is increasing evidence that long noncoding RNAs are involved in hepatocellular carcinoma (HCC) tumorigenesis. The expression level of TRPM2-AS in HCC and its clinical association remain poorly defined. Method qRT-PCR was performed to detect the expression of TRPM2-AS in 108 HCC patients. The correlations between TRPM2-AS expression and clinicopathological factors and prognosis were evaluated. The inference of TRPM2-AS to the proliferation and apoptosis of HCC cells was detected. Aims The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…These results demonstrated that TRPM2-AS might work as an oncogene and play crucial roles in glioma progression. Previous studies suggested the promotion of cell apoptosis after the silencing of TRPM2-AS in prostate cancer, liver cancer, and non-small-cell lung cancer Ma et al, 2017;Xu et al, 2018). Whether TRPM2-AS participates in glioma cell apoptosis or not is still a problem in need of further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrated that TRPM2-AS might work as an oncogene and play crucial roles in glioma progression. Previous studies suggested the promotion of cell apoptosis after the silencing of TRPM2-AS in prostate cancer, liver cancer, and non-small-cell lung cancer Ma et al, 2017;Xu et al, 2018). Whether TRPM2-AS participates in glioma cell apoptosis or not is still a problem in need of further study.…”
Section: Discussionmentioning
confidence: 99%
“…TRPM2-AS is an antisense lncRNA mapped to 44 658 901-44 669 874 position of TRPM2 gene (Orfanelli et al, 2008). It was demonstrated to be an oncogene for non-small-cell lung cancer, prostate cancer, and hepatocellular carcinoma (Huang et al, 2017;Orfanelli et al, 2015;Xu et al, 2018). However, its effects in gliomas are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TRPM2-AS was reported to be up-regulated in breast cancer to promote uncontrollable proliferation and weaken breast cancer cells' apoptosis through binding with miR-140-3p [14]. Besides, TRPM2-AS was up-regulated in hepatocellular carcinoma (HCC) tissues than in normal adjacent tissues, and it had a significant correlation with tumor size, differentiation, and the prognosis outcome of HCC patients [16]. Compared with previous studies, our results had the similar conclusion that TRPM2-AS was up-regulated in BLCA to promote the cell viability and cell proliferation, and inhibit cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The host gene of TRPM2-AS, transient receptor potential cation channel subfamily M member 2 antisense RNA, consists of 3 exons and locates at chromosome 21q22.3. TRPM2-AS was first discovered to be up-regulated in melanoma in 2008 [10], and it was gradually found that to be a cancer-promoting gene in more other tumors including reproductive system tumors, digestive system tumors and respiratory system tumors [11][12][13][14][15][16][17]. Yet, there have been no researches exploring how TRPM2-AS implements a marked effect in BLCA.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 TRPM2-AS locates at human chr21q22.3, and consists of 875 nucleotides with three exons in the translation template. 12 TRPM2-AS has been revealed to be upregulated and involved in the progression of melanoma, 12 non-small cell lung cancer, 13,14 hepatocellular carcinoma, 15 and prostate cancer. [16][17][18] The expression status and function of TRPM2-AS were still in osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%